2013
DOI: 10.1002/jmv.23831
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human papillomavirus genotypes, assessment of HPV 16 and 18 viral load and anal related lesions in HIV positive patients: A cross‐sectional analysis

Abstract: Natural history of anal intraepithelial neoplasia and anal cancer is not fully understood. Factors associated with cytological abnormalities and predictors of progression to high-grade anal intraepithelial neoplasia still deserve investigation. The aim of this cross-sectional study was to assess the prevalence of HPV types, the relationship between HPV genotypes, HPV 16/18 viral load and cytological abnormalities in male and female HIV-infected patients. One hundred and twenty-two (72.6%) patients were infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The fact that only 10% of the anal swabs were not collected appropriately indicates that the anal self-sampling strategy is efficient. In addition, in the present study, the rates of detection of the main HPV types and the median HPV16 and 18 DNA loads were similar to those observed in a previous study in HIV-infected male and female patients who had anal samples collected by the clinician in another center of Marseille University Hospitals [19]. This further validates anal self-sampling for HPV detection and quantification.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The fact that only 10% of the anal swabs were not collected appropriately indicates that the anal self-sampling strategy is efficient. In addition, in the present study, the rates of detection of the main HPV types and the median HPV16 and 18 DNA loads were similar to those observed in a previous study in HIV-infected male and female patients who had anal samples collected by the clinician in another center of Marseille University Hospitals [19]. This further validates anal self-sampling for HPV detection and quantification.…”
Section: Discussionsupporting
confidence: 71%
“…Demographic characteristics and the most recent CD4 cell count and HIV RNA load were obtained from the clinical records. HPV DNA detection, HPV16/18 DNA quantification, HPV genotyping and cellular DNA quantification were performed as previously described [19]. HPV genotyping was performed by PCR (using MY09/MY11 primers), Sanger population sequencing, and then phylogenetic analysis; in case of mixed sequence profiles, PCR products were cloned using PGEM Easy Plasmid (Promega) prior sequencing, as previously described [20].…”
Section: Methodsmentioning
confidence: 99%
“…Goldstone et al showed that the risk of high-grade anal dysplasia was 77 % higher in HPV-positive than in HPV-negative homosexual men; the combination of HPV detection with liquid-based anal cytology improved sensitivity and PPV [18][19][20]. A high HPV viral load (C5.3 log 10 / 10 6 cells) was also associated with abnormal cytology [21]. Although viral titers were not measured in this study, oncogenic HPV is highly associated with cytological abnormality, but not associated with histological high-grade AINs.…”
Section: Discussionmentioning
confidence: 93%
“…The use of a HPV-16 cut-off value of 65 increased the specificity (0.77) to better differentiate grade of lesions, demonstrating that quantitative HPV-16 detection using the cut-off value of 65 copies per cell may predict high-grade disease and is in better agreement with AB (0.649) than AC (0.557) or qualitative HPV-16 HPV detection (0.258). Genotyping studies have shown that HPV-16 DNA is frequently detected in anal specimens and is associated with anal dysplasia/cancer; however, there is limited data about variation in HPV copy numbers across AC and AB grades [20,21]. Our findings suggest that HPV-16 quantitation may be useful in disease classification during screening for anal dysplasia/cancer.…”
Section: Discussionmentioning
confidence: 70%